Development and verification of a mathematical model for the specific resistance of a curved subsoiler. (February 2020) - Jiang, Xiaohu; Tong, Jin; Ma, Yunhai; Sun, Jiyu
Abstract : A subsoiler is an important implement in no-tillage agriculture that can keep the soil in a good condition and increase crop yields. The prediction and reduction of the draught force of subsoilers are vital for improving the efficiency of subsoilers and saving energy. In this paper, a mathematical-analytical model considering the subsoiler geometry, soil properties and working conditions was developed for predicting the draught force of a curved subsoiler. In addition, three curved subsoilers that were adapted for three different working depths were designed according to the model to reduce the draught force and energy consumption. Field experiments were conducted to validate the model and compare the draught force, soil disturbance area and specific resistance of the designed subsoilers with conventional ones. The results showed that the correlations between the measured and predicted draught force, soil disturbance area and specific resistance were significant, which meant that the model could be used to predict the performance of a curved subsoiler. The three designed subsoilers had smaller draught forces and specific resistances than those of conventional subsoilers at their designed working depths, so the designed subsoilers exhibited better performance at their designed working depths than conventional subsoilers. Therefore, the model developed in this paper was useful for predicting the draught force of curved subsoilers and designing a subsoiler with low specific resistance. Highlights: It is efficient to design subsoilers according to required tillage depths. A model can be used to design curved subsoilers with low specific resistance. Subsoilers exhibit better performance at their designed working depths.